Building a Healthy Economy from the Bottom Up : Harnessing Real-World Experience for Transformative Change - Flaccavento, Anthony (Book collections on Project MUSE., 2016)
The global economy has witnessed important changes in recent years. In the United States, enterprising communities have transitioned from tobacco farming to growing organic produce, from extractive fishing to vertical farming, from nonrenewable energy consumption to the implementation of solar cooperatives -- and have transformed from impoverished neighborhoods into green development zones. Yet these promising achievements remain a small part of the total economy and are largely ignored by policy makers, pundits, and economists. In Building a Healthy Economy from the Bottom Up: Harnessing Real World Experience for Transformative Change, Anthony Flaccavento introduces readers to the innovators who are creating thriving, locally based economies and provides a road map for others who are interested in doing the same. He demonstrates that, despite the success of local initiatives like farmers' markets and clean energy cooperatives, true and lasting change of this type stalls without the appropriate discussion and implementation of public policies that define their lasting impact. He shows how active citizens can spur essential changes, generate community capital, increase civic dialogue, and foster sustainability efforts. Flaccavento skillfully combines economic analysis and public policy recommendations with practical solutions. His call to collective action will appeal to scholars, entrepreneurs, policymakers, community activists, environmentalists, and all citizens passionate about the health of their communities.